Size and soft budget constraints - Ernesto Crivelli; Klaas Staal (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
There is much evidence against the so-called too big to fail hypothesis in the case of bailouts to sub-national governments. We look at a model where districts of different size provide local public goods with positive spillovers. Matching grants of a central government can induce socially-efficient provision, but districts can still exploit the intervening central government by inducing direct financing. We show that the ability of a district to induce a bailout from the central government and district size are negatively correlated.
urn:nbn:de:bvb:19-epub-13379-8
Keywords: H4; H7; R1; 330; bailouts; soft-budget constraints; jurisdictional size; public goods; spillovers